The Value of Diagnostic Laparoscopy in Gastroenterology (Due to 3000 cases) - Atilla ÖKTEN; Süleyman YALÇIN; Güngör BOZTAŞ; Oktay YEĞİNSÜ and Sadakat ÖZDİL and Zeynel MUNGAN and Yılmaz ÇAKALOĞLU and Sebahattin KAYMAKOĞLU and İlhan ULAGAY (Turkish Journal of Gastroenterology, 2020)
-